Análise de alterações comportamentais e neuroquímicas em ratas submetidas ao modelo experimental de endometriose induzida por transplante autólogo de tecido uterino - Lima Filho, Paulo Wagner Linhares (2018)
Endometriosis is a chronic and progressive gynecological disease that affects about 10% of women of reproductive age. High rates of depression, anxiety and emotional stress are often found in these patients. However, little is known about the mechanisms underlying the development and establishment of endometriosis and its psychiatric comorbidities. Animal models provide a useful tool for studying the temporal sequence and biological pathways involved in this disease, as well as in comorbid states, such as neuropsychiatric disorders. Therefore, in the present study, we aimed to evaluate the main behavioral changes and pain sensitization in the animal model of peritoneal endometriosis. Also, levels of markers of oxidative damage and hippocampal neurotrophins were evaluated. For this, adult female Wistar rats were submitted to the model of peritoneal endometriosis induced by autologous uterine tissue transplantation. The rats were evaluated weekly for three weeks for the development of anxiety-type and depressive-type behaviors, as well as changes in peripheral and visceral sensitization to pain. The results demonstrated that the administration of reserpine induced a depression-like behavioral pattern, by increasing the immobility time of the animals in both the tail suspension test and forced swimming, without altering the locomotor activity of the animals. associated with sitagliptin, especially at the highest dose (6 mg / kg). Serum levels of corticosterone were measured and, in the hippocampus, the markers of oxidative stress - reduced glutathione concentration (GSH), levels of lipid peroxidation and myeloperoxidase activity (MPO) - as well as neurotrophin brain factor expression brain (BDNF). According to our results, the major behavioral changes started 2 weeks after the induction of the model. In fact, the rats with endometriosis on the 14th day of evaluation presented type-anxiety changes in the open field test and the high cross labyrinth, but only on the 21st day, type-depressive changes were identified in the forced swimming test. Rats with endometriosis presented a simultaneous reduction in the peripheral sensory pain threshold from the second week of induction, in addition to an increase in serum corticosterone levels in response to an acute stressor event. In the hippocampus, dissected on days 7, 14 and 21 of the surgical procedure, the peritoneal endometriosis model caused a marked increase in oxidative damage, demonstrated by the decrease in GSH concentrations, increase of lipid peroxidation and increase of MPO enzyme activity. A time-dependent reduction of BDNF levels in the hippocampus of rats submitted to the endometriosis model was also induced. Interestingly, most of these oxidative and neurochemical changes occurred in a time-related manner, being more evident in the third week of induction of the model, when also the main behavioral changes occurred. Therefore, this study demonstrates that the present model of endometriosis mimics several neuropsychiatric symptoms evidenced in the clinical setting of patients with endometriosis. Also, our findings advocate for the participation of an imbalance of the oxidative state and hippocampal trophic support for the appearance of these alterations. Thus, the present model constitutes a valuable tool to investigate new therapeutic strategies for both the endometriosis-related pain symptoms and its neuropsychiatric comorbidities. Keywords: Endometriosis. Depression. Anxiety. Hippocampus